Individual Claims-making in the Terri Schiavo Case. (December 2015) - Rohlinger, Deana A.; Vaccaro, Christian; Naiman-Sessions, Miriam; Mauney, Heather
This article uses unique data to explore individual claims-making on the Terri Schiavo case. We analyze 2, 509 e-mails sent to Jeb Bush and 1, 182 newspaper stories about the Schiavo case to assess how mass media, claims-makers, and individual experience affect the frames and identities used to support or oppose intervention on Terri's behalf. We find that the frames individuals use vary according to whether they support Bush's involvement in the case. In addition, we find that the frames individuals use in their claims-making do not always mirror those discussed in mass media. Specifically, the frequency with which e-mailers discuss particular ideas varies according to the engagement of claims-makers on the issue as well as the complexity of the frame. Finally, we find that some individuals do deploy identities strategically in their e-mails. Opponents of intervention, for instance, use their political identities as Republicans to urge Bush to stay out of the case. Not all identity deployment, however, corresponds with support or opposition to Bush's involvement on the Schiavo case. Individuals use their familial and religious identities to both support and oppose intervention. We conclude with a discussion of the relevance of these findings for understanding claims-making in the twenty-first century.